Numerical Investigation of Influence of Temperature on Propagation of Ultrasonic Waves in Waveguides with Mode Conversion - Jasiūnienė, Elena; Zukauskas, E.; Kazys, R. (Elektronika ir Elektrotechnika, 2012)
In the case of the objects with a high temperature the measurements are often performed using waveguides in order to protect the ultrasonic piezoelectric transducers from a high temperature. In some cases, for measurement of specific properties of materials, shear waves are used. Shear waves can be generated exploiting mode conversion phenomenon using a longitudinal wave transducer and a waveguide with deflected front surface. However, the deflection angle has to be carefully selected, when it is required that the shear waves would propagate parallel to the waveguide axis. The proper deflection angle depends on material used for the waveguide properties. When the temperature changes, the properties of the material (as ultrasonic velocity) change as well, causing the change of the reflection angle and the propagation path. A numerical investigation was performed in order to evaluate how the change of the temperature will influence the reflection angle of the ultrasonic waves and the propagation path. It is shown that the change of the temperature influences the reflection angle and propagation path of ultrasonic waves and should be taken into account. DOI: http://dx.doi.org/10.5755/j01.eee.18.10.2537